SINTESIS TIO2-KAOLIN DAN UJI AKTIVITAS FOTOKATALISIS UNTUK ANTIBAKTERI Escherichia Coli DAN Staphylococcus aureus - Desi Listiani; Ajuk Sapar; Anthoni Batahan Aritonang (Indonesian Journal of Pure and Applied Chemistry, 2019)
Synthesis of TiO2-kaolinite has been performed using solgel method with titanium tetraisopropoxide (TTIP) as precursor. Synthesis of TiO2-kaolinite by temperature calcination 450 °C for 2 hours to obtain TiO2-kaolinite anatase and then the antibacterial photocatalysis activity of E. coli and S. aureus was performed. Identification of the characteristics TiO2-kaolinite used XRD, SEM, FTIR, and DR-UV. It was found that TiO2-kaolinite has been anatase phase structure with the particle size is 19-103 nm, and have a spheric morphology. Infrared spectra indicate a specific group in wave number 921 cm-1. The antibacterial photocatalysis activity test was performed in liquid media and  measurements by the Optical Density (OD) is using Spectrophotometer UV-Vis at wavelength of 600 nm. The results photocatalysisis activity of TiO2-kaolinite for E.coli, TiO2-kaolinite can kill bacteria occured in the 60th minute, while for S. aureus TiO2-kaolin can kill bacteria occured in the 100th minute. Our results clearly that the TiO2-kaolinite has potential as an antibacterial material in water sterilization.